PENGARUH KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT BANK HIBANK INDONESIA DI JAKARTA BARAT - Safiih, Abdul Rahman; Aryanti, Aprilia Putri (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine Communication and Work Discipline on Employee Performance at PT Bank Hibank Indonesia in West Jakarta, both partially and simultaneously. The type of research used is a descriptive quantitative method. The population taken from all employees at PT Bank Hibank Indonesia in West Jakarta was 75 people. Sampling used a saturated sample of 75 respondents. Hypothesis testing using communication variables on employee performance obtained t count > t table or (2.928 > 1.993), this is also strengthened by the ???? value < Sig. 0.05 or (0.000 < 0.05). This means that there is a significant influence by the communication variable (X1) on the performance variable (Y). The experimental hypothesis test of the work discipline variable on employee performance obtained a calculated t value > t table or (2.903 > 1.993), this was also strengthened by the ???? value <Sig. 0.05 or (0.000 < 0.05). This means that there is a significant influence by the work discipline variable (X2) on employee performance (Y). Simultaneously testing the hypothesis of communication and work discipline variables on employee performance obtained a calculated F value > F table or (96.453 > 3.12), this was also reinforced by the ???? value < Sig, 0.05 or (0.000 < 0.05). This means that there is a significant simultaneous influence of the communication and work discipline variables on employee performance. The research results of communication and work discipline have a positive and significant effect on employee performance with the regression equation Y = 4.858 + 0.375 X₁ + 0.484 The value of determination or contribution of influence is 72.8%, the remaining 27.2%.